Workshop Media Pembelajaran Atraktif berbasis Power Point Audio Visual di Madrasah Ibtidaiyah Muhammadiyah Parakan Karanganyar - Muhroji Muhroji; Hengki Hermawan; Frendy Sulistyo; Farida Kurniawati Utami; Muhamad Taufik Hidayat; Lina Wahyu Fatmasari (LPPM Universitas Timor, 2021)
The aims of this community service was to provide knowledge and skills on how to make a good and interesting PowerPoint (PPT) slide. In addition, this community service also aims to provide a skill to make an educational game, and to make a teaching material from PPT by including audio and viisual. The community service at Madrasah Ibtidaiyah Muhammadiyah Parakan (MIM Parakan) Karanganyar, Central Java was attended by the principal and twenty seven teachers. Before doing this community service, there are various preparations such as; ask for permission from the faculty to carry out activities, then give service permits to partner schools, prepare various needs and carry out activities that have been coordinated between the team and the partner schools. This activity was very enthusiastically followed by teachers at MIM Parakan..